PEMERATAAN LINI PRODUKSI DENGAN MENGGUNAKAN PENDEKATAN LINE BALANCING DAN TIME STUDY UNTUK MENINGKATKAN EFISIENSI DI PT. XYZ - Irene Fritzdwina (2022)
PT. XYZ is a company that produces bras and briefs with the production of more than 450 styles every year, either styles that are produced continuously, seasonal, or one-time production. This study uses the line balancing method to balance the assembly line to be more effective and efficient. The results obtained from this study for line balancing styles Y52075, YZPE, and YZBDW are by comparing Ranked Position Weight, Region Approach and Largest Candidate Rule methods with different results. From the analysis of the analysis of the three methods for the Y50275, YZPE, and YZBDW styles, the best is the Ranked Position Weight (RPW) method because it has efficiency values of 66.922%, 70.677%, and 75.156%. The Balance Delay values are 33.078%, 29.323%, and 24.844%. The smoothness index values are 162,755, 173,500, and 122,954 seconds. After that, the approach is carried out using a simulation model with Arena Software. The results of the actual and proposed models show that the proposed simulation results have an increase in the average output.